PERAN SELF-AWARENESS DAN EGO SUPPORT TERHADAP KEPUASAN HIDUP REMAJA TIONGHOA - Agoes Dariyo (PSIKODIMENSIA, 2016)
The objective of this study was to investigate the impact of the self-awareness and ego support on the life satisfaction of adolescence. Participants were 223 subjects (19-21 years). Collecting data by using questionnaires such as: selfawareness, ego support, and the life satisfaction of adolescence. Data was analyzed with multiple regression via SPSS 16.0 software program. Found was the impact of self-awareness on life satisfaction (r2 = .052, t = 3.467 , p = .001 < .01), the impact of ego support on life satisfaction (r2 = 0,219, t = 7.877, p = 0,000 < 0,01), and the impact of self-awareness and ego support on the life satisfaction of adolescence (r2 = 0,.243, F = 35.307, p =0, .000 < 0,01).